Effect of partial substitution of wheat flour with okara flour in the elaboration of panettone - Ponce Aquino, Víctor T. (2024)
“Okara” is an industrial residue generated from the production of soy milk. This residue can be transformed into okara flour, a higher value-added product that can be used in the baking industry. The main objective of this research is to determine the optimal substitution of wheat flour with okara flour without altering the process or the rheological characteristics in the preparation of panettone. As part of the methodology, the following technological characteristics were evaluated: fibre size, moisture percentage, height variations, final product weights, variation in beating times, acidity, and water activity. The results of this research showed that the optimal substitution of okara flour in the panettones is 4.2% (okara flour/wheat flour ratio of 0.05/1), resulting in characteristics similar to a standard panettone (without substitution), with a higher percentage of water retention that helps extend the product shelf-life. Hedonic scale evaluation demonstrated that panettones with 4.2% of okara flour did not present significant differences compared with panettones prepared with wheat flour only. In addition to the results obtained, it is shown that with greater substitution rates, there are technological variations in the size and formation of the gluten network. In conclusion, okara flour can be applied in the preparation of panettones with an optimal substitution of 4.2%, with 8.7% and 13.7% substitutions not recommended according to the tests carried out in the investigation.